2021
DOI: 10.31234/osf.io/vmurs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Usual Care Outcomes in Major Depression in Youth by Targeting Memory Specificity: A Randomized Controlled Trial of Adjunct Computerised Memory Specificity Training (c-MeST)

Abstract: Objective: Memory Specificity Training (MeST) improves the recall of past personal experiences, an impairment in Major Depressive Disorder (MDD). Extending on previous findings that computerised MeST (c-MeST) improves memory specificity and depressive symptoms in adults, this study aimed to answer two questions: 1) does c-MeST improve memory specificity and depressive symptoms in youth with MDD; and 2) does c-MeST improve memory specificity and depression in addition to other treatment? Methods: Participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While anticipatory pleasure was clearly lower in the MDE group, the lack of correlation with specificity suggests that the adolescents used different ways of conceptualising future reward aside from drawing on specific autobiographical thoughts. On this note, specific interventions for autobiographical thinking (Hallford and Mellor, 2016; Hallford et al, 2022) and memory specificity (Hallford et al, 2021) have been validated for use in youth populations, and future specificity training in clinical depression in adults (Hallford et al, 2023). Similar work can be attempted in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While anticipatory pleasure was clearly lower in the MDE group, the lack of correlation with specificity suggests that the adolescents used different ways of conceptualising future reward aside from drawing on specific autobiographical thoughts. On this note, specific interventions for autobiographical thinking (Hallford and Mellor, 2016; Hallford et al, 2022) and memory specificity (Hallford et al, 2021) have been validated for use in youth populations, and future specificity training in clinical depression in adults (Hallford et al, 2023). Similar work can be attempted in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Access to autobiographical memory is important because it is associated with adaptive cognitive processes such as decision-making, planning, and problem-solving ability (Dalgleish & Werner-Seidler, 2014). Interventions targeting memory specificity have already been shown to reduce depressive symptoms in youth (Hallford, Austin, et al, 2021; Neshat-Doost et al, 2012). Further, studies have found that when people perceive life stories that are strongly derived from personal experiences, a healthy identity/self-concept revealed through these stories is associated with less depression symptomatology, including among young adults (Hallford & Sharma, 2019; Hallford et al, 2022; Hallford & Mellor, 2016; Hallford & Mellor, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Models of autobiographical memory (Conway and Pleydell-Pearce, 2000) propose that autobiographical knowledge is stored in a fluid manner, such that prior experience can be recalled as generalised summaries which characterise categories of events (i.e., categoric memories) or extended periods of time (i.e., extended memories), or conversely, as specific, single incident events which are isolated in space and time and contain a high level of detail (i.e., specific memories). The ability to retrieve specific memories has been implicated in the onset and maintenance of multiple mental health disorders (Barry et al, 2021;Hallford et al, 2021a), including the primary onset of symptoms (Askelund et al, 2019). Further, reduced ability to retrieve specific, single-incident memories appears to be a marker of higher chronicity of symptoms, as it is associated with increased frequency of depressive episodes and suicide attempts (Williams and Broadbent, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions targeting memory specificity have already been shown to reduce depressive symptoms in youth (Hallford et al, 2021;Neshat-Doost et al 2012).…”
mentioning
confidence: 99%
“…However, to the authors' knowledge, no study to date has examined whether adolescents with major depression also have impairments in future thinking specificity. So, while interventions targeting future thinking specificity have shown this can be improved in adults (Hallford et al 2020b), and in clinically depressed adult samples where reductions in depression are also observed (Hallford, Rusanov, et al, 2021), it is unclear whether this might also be a potential target for interventions in adolescents.…”
mentioning
confidence: 99%